The complete RCA Victor recordings - Armstrong, Louis 1901-1971; Keepnews, Orrin (New York, NY BMG Classics, 1997)
Performed by Louis Armstrong and his orchestra.
Disc 4. It takes time / A. Korb (2:37) -- You don't learn that in school / R. Alfred, M. Fisher (2:41) -- Ain't misbehavin' / A. Razaf, F. Waller, H. Brooks (3:56) ; Rockin' chair / H. Carmichael (5:14) ; Back o' town blues / L. Armstrong, L. Russell (4:13) ; Pennies from heaven / J. Burke, A. Johnston (3:42) ; Save it pretty mama / P. Denniker, D. Redman, J. Davis (4:28) ; St. James Infirmary (with his All Stars) / J. Primrose (3:37) -- Jack-Armstrong blues / L. Armstrong, J. Teagarden (2:58) -- Rockin' chair / H. Carmichael (3:04) -- Some day you'll be sorry / L. Armstrong (3:11) -- Fifty-fifty blues / B. Moore Jr. (2:57) -- A song was born / D. Raye, G. DePaul (3:18) ; Please stop playin' those blues, boy / C. Demetrius, F. Moore (3:16) -- Before long / C. Sigman, S. Catlett (2:51) ; Lovely weather we're having (with his All Stars) / J. DeVries, J. Bushkin (3:15) -- Rain, rain / H. Stanley, I. Taylor (2:37) ; Never saw a better day / H. Stanley, I. Taylor (3:10).
Title from container.
Reissues, with 8 previously unreleased tracks.
Program notes by Dan Morgenstern (35 pages : portraits) laid in container.
Reissue produced by Orrin Keepnews.
Louis Armstrong, vocals, trumpet ; with his Orchestra unless otherwise noted.
111654
Keywords: Jazz; Jazz vocals; Trumpet music (Jazz); Blues (Music); jazz; Alternate takes (Sound recordings); Blues (Music); Songs; Versions alternatives (Enregistrements sonores)